2015
DOI: 10.1128/aac.04222-14
|View full text |Cite
|
Sign up to set email alerts
|

The Mycobacterium tuberculosis Outer Membrane Channel Protein CpnT Confers Susceptibility to Toxic Molecules

Abstract: Mycobacterium tuberculosis, the causative agent of tuberculosis, is protected from toxic solutes by an effective outer membrane permeability barrier. Recently, we showed that the outer membrane channel protein CpnT is required for efficient nutrient uptake by M. tuberculosis and Mycobacterium bovis BCG. In this study, we found that the cpnT mutant of M. bovis BCG is more resistant than the wild type to a large number of drugs and antibiotics, including rifampin, ethambutol, clarithromycin, tetracycline, and am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…These results indicated that the function of the outer membrane as a permeability barrier is not impaired by the loss or overproduction of Rv0888. These results also show that the putative outer membrane channel of full‐length Rv0888 does not increase the susceptibility of Mtb to the tested antibiotics in contrast to the porin MspA of M. smegmatis (Mailaender et al ., ; Stephan et al ., ) or the autotransporter CpnT of Mtb (Danilchanka et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These results indicated that the function of the outer membrane as a permeability barrier is not impaired by the loss or overproduction of Rv0888. These results also show that the putative outer membrane channel of full‐length Rv0888 does not increase the susceptibility of Mtb to the tested antibiotics in contrast to the porin MspA of M. smegmatis (Mailaender et al ., ; Stephan et al ., ) or the autotransporter CpnT of Mtb (Danilchanka et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, expression of a non‐catalytic Rv0888 mutant was detrimental even for the already impaired Δ rv0888 mutant of Mtb. This observation is consistent with previous findings that the presence of proteins with channel activity in the outer membrane makes Mtb more susceptible to toxic solutes such as nitric oxide produced by macrophages to control growth of Mtb (Fabrino et al ., ; Danilchanka et al ., ). However, mouse infection experiments did not reveal a virulence defect of the Mtb Δ rv0888 mutant.…”
Section: Discussionmentioning
confidence: 97%
“…189 The contribution of CpnT to in vitro resistance of large, hydrophilic drugs including STR was only moderate. 190 …”
Section: Cell Membrane Modificationmentioning
confidence: 99%
“…The MspA protein in M. smeg-matis is the best characterized mycobacterial porin but has no orthologue in M. tuberculosis (129). More recently, CpnT (Rv3903c) was identified as a mycobacterial toxin and water-filled protein channel that promotes the uptake of glycerol and hydrophilic and hydrophobic antibiotics (131,132).…”
Section: Esx Systems and Envelope Permeabilitymentioning
confidence: 99%
“…In mycobacteria, relatively few proteins that function as channels through the MOM have been characterized (128)(129)(130)(131). The MspA protein in M. smeg-matis is the best characterized mycobacterial porin but has no orthologue in M. tuberculosis (129).…”
Section: Esx Systems and Envelope Permeabilitymentioning
confidence: 99%